NUDIBRANCHIA DENSITY AND DIVERSITY IN SPERMONDE ISLANDS, SOUTH SULAWESI - Abdul Haris; Ahmad Bahar; Syafiuddin; Asrul, Asrul; Yasir, Inayah (Hasanuddin University, 2021)
Nudibranchia is one of the interesting and unique organisms because it has different shapes, sizes and colors attracting tourists when doing snorkeling and diving activities. However, because the distribution of marine biota is very dependent on habitat conditions and the availability of food types, it affects the density and diversity of Nudibranchia in the waters. The purpose of this study was to determine the density and diversity of Nudibranchia species. This research was conducted in March-April 2021 on Samalona Island, Barranglompo Island, and Badi Island in the Spermonde Islands, South Sulawesi. The method used is the Belt Tansect method with a length of 100 m with a sweep of 2.5 m to the left and right, at a depth of 4-7 m. Based on the results of the study, the number of Nudibranchia species found on Samalona Island was 4 families, 7 species, and 36 individuals; on Barranglompo Island as many as 4 families, 6 species, and 51 individuals; while on Badi Island there are 3 families, 6 species, and 30 individuals. Nudibranchia density on Samalona Island is 0.024 ind/m2, on Barranglompo Island is 0.034 ind/m2, while on Badi Island it is 0.020 ind/m2. The value of the Nudibranchia Diversity Index on Samalona Island is 1.14; on Barranglompo Island by 0.96; and on Badi Island it was 1.28 with a diversity community structure that was quite stable to stable on each island. Substrate cover conditions found on each island were dominated by Dead Coral Algae (DCA), on Samalona Island at 58.33%; Barranglompo Island by 54.90%; and Badi Island by 66.67%. Keywords: Nudibranchia, density, diversity, Samalona Barranglompo, Badi.